INNOVATIVE TEXTILES INDUSTRY AND ITS FUTURE WITHIN THE CONCEPT OF CIRCULAR ECONOMY – FROM THE GLOBAL TO REGIONAL PERSPECTIVE - WYSOKIŃSKA, ZOFIA (Journal of Vasyl Stefanyk Precarpathian National University, 2019)
The paper deals with the complex analyses of production, export and import of products in the textile industry in different countries of the world. The largest manufacturers and exporters of textile products are identified. Trends in production capacity changes in the industry over the past years are analysed. The place and role of textile industry development in the context of the implementation of the circular economy principle in line with the EU priorities are substantiated. The main directions of perspective development of the textile industry are identified. Two main national documents that have been developed in Poland which set out the current development directions of the country in the field of sustainable development and environmental protection: Strategy for Responsible Development until the year 2020 (with the perspective until the year 2030) and National Waste Management Plan elaborated in the year 2014. The article provides a detailed analysis of the development of regional industry, including the textile industry based on the city of Lodz (Poland). The identified areas of smart specialisations of the Region of Lodz include the following sectors of economic activity: modern textile and fashion industry; advanced building materials; medicine, pharmacy, and cosmetic industry; power generation (including Renewable Energy Sources); innovative agriculture and agricultural and food processing; computer science and telecommunication. The paper proposes the main directions of the textile industry development in the example of Poland: 1) generation of minimal waste in the production process (1R - with application of the most innovative technology), 2) its maximum re-use (2R), 3) application of the third method within the three R formula (reduce, reuse, recycle) which is recycling (3R), the awareness of the importance of which among producers and citizens in many countries is systematically growing.